Learning organization in social work institutions - Vîșcu, Loredana Ileana; Rad, Dana; Cădariu, Ioana Eva; Pintea, Florentina-Anica (Technium Social Sciences Journal, 2025)
Organizational culture plays a critical role in shaping the values, behaviors, and operational dynamics of social work institutions. This paper explores the multifaceted nature of organizational culture, emphasizing its impact on institutional effectiveness, adaptability, and sustainability. Drawing on theoretical frameworks and empirical studies, the analysis highlights the interplay between organizational values, leadership, supervision, and innovation in fostering a learning-oriented and inclusive environment. Challenges such as resource constraints, resistance to change, and staff burnout are examined alongside opportunities for growth through technological integration and authenticity. The discussion underscores the need for a balanced approach that combines stability with innovation to address evolving societal needs. The findings offer valuable insights for policymakers, practitioners, and educators, providing a foundation for building resilient and adaptive social work institutions.